The impact of a developing community on the water quality of an urban river - Pretorius, Lize; De Villiers, Gawie (University of the Free State, 2003)
The influence of a developing community on the water quality of an urban river is illustrated in this article. Testing revealed high chemical, physical and microbiological variables, indicating relatively serious pollution. A pollution cycle exists which can only be destroyed by addressing the socio-economic issues influencing water quality.

Die invloed van ’n ontwikkelende gemeenskap op die waterkwaliteit van ’n stedelike rivier word in die artikel aangetoon. Toetse het op ’n groot aantal chemiese, fisiese en mikrobiologiese veranderlikes gedui wat ’n betreklik ernstige besoedelingstoestand aandui. ’n Besoedelingsiklus bestaan wat slegs vernietig kan word deur die sosio-ekonomiese probleme, wat ’n impak op waterkwaliteit het, aan te spreek.
Keywords: Water quality; Water Quality Management Plan; Pollution; Developing communities; Urban rivers